Not only acute respiratory failure: COVID-19 and the post-intubation/tracheostomy upper airways lesions† - Brascia, Debora; De Palma, Angela; Cantatore, Mirko Girolamo; Pizzuto, Ondina; Signore, Francesca; Sampietro, Doroty; Valentini, Mariangela; Genualdo, Marcella; Marulli, Giuseppe (Frontiers in Surgery, 2023)
Background: An increasing number of patients have been subjected to prolonged invasive mechanical ventilation due to COVID-19 infection, leading to a significant number of post-intubation/tracheostomy (PI/T) upper airways lesions. The purpose of this study is to report our early experience in endoscopic and/or surgical management of PI/T upper airways injuries of patients surviving COVID-19 critical illness. Materials and Methods: We prospectively collected data from patients referred to our Thoracic Surgery Unit from March 2020 to February 2022. All patients with suspected or documented PI/T tracheal injuries were evaluated with neck and chest computed tomography and bronchoscopy. Results: Thirteen patients (8 males, 5 females) were included; of these, 10 (76.9%) patients presented with tracheal/laryngotracheal stenosis, 2 (15.4%) with tracheoesophageal fistula (TEF) and 1 (7.7%) with concomitant TEF and stenosis. Age ranged from 37 to 76 years. Three patients with TEF underwent surgical repair by double layer suture of oesophageal defect associated with tracheal resection/anastomosis (1 case) or direct membranous tracheal wall suture (2 cases) and protective tracheostomy with T-tube insertion. One patient underwent redo-surgery after primary failure of oesophageal repair. Among 10 patients with stenosis, two (20.0%) underwent primary laryngotracheal resection/anastomosis, two (20.0%) had undergone multiple endoscopic interventions before referral to our Centre and, at arrival, one underwent emergency tracheostomy and T-tube positioning and one a removal of a previously positioned endotracheal nitinol stent for stenosis/granulation followed by initial laser dilatation and, finally, tracheal resection/anastomosis. Six (60.0%) patients were initially treated with rigid bronchoscopy procedures (laser and/or dilatation). Posttreatment relapse was experienced in 5 (50.0%) cases, requiring repeated rigid bronchoscopy procedures in 1 (10.0%) for definitive resolution of the stenosis and surgery (tracheal resection/anastomosis) in 4 (40.0%). Conclusions: Endoscopic and surgical treatment is curative in the majority of patients and should always be considered in PI/T upper airways lesions after COVID-19 illness.